Dinosaurs as skeletons or lifelike replicas - effects on interest in extinct animals - Kubi, Michael; Kleespies, Matthias Winfried; Wenzel, Volker (Frontiers in Ecology and Evolution, 2025)
IntroductionSince their discovery Dinosaurs have attracted the interest of scientists and the general public alike, and are therefore an attractive way of introducing students to various aspects of the Earth's history and stimulating their interest. There are different types of dinosaur exhibitions, ranging from original excavation sites to theme parks, all with varying levels of scientific accuracy and authenticity.MethodsIn this study we developed and conducted a guided tour of a dinosaur exhibition in a natural history museum, showing dinosaur fossils or their replicas and a special dinosaur exhibition with lifelike animatronic models in a zoo. We investigated the effect on interest in extinct, prehistoric animals in these dinosaur exhibitions.ResultsThe results show that the skeletons in a natural history museum showed a significant increase in interest, while the lifelike animatronics had no effect. An examination of the gender results shows that boys were the main contributors to the increase in interest in extinct animals.DiscussionThe main reason for this difference may be that natural history museums, with their original dinosaur fossils (or detailed replicas, which are legitimate substitutes for original objects), provide a more authentic atmosphere that arouses interest, curiosity and surprise, something that the lifelike dinosaur models could not do. However, these effects were not long-lasting, as demonstrated by follow-up tests.